Facile Template In-Situ Fabrication of ZnCo2O4 Nanoparticles with Highly Photocatalytic Activities under Visible-Light Irradiation - Vu T. Tan; La The Vinh; Tran Ngoc Khiem; Huynh Dang Chinh (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
High specific surface area ZnCo2O4 nanoparticles were prepared via a sacrificial template accelerated hydrolysis by using nanoparticles of ZnO with highly polar properties as a template. The obtained ZnCo2O4 nanoparticles were characterized by the method of scanning electron microscopy (SEM), X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET) surface area measurements, Transmission electron microscopy (TEM), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). The obtained nanoparticles were performed as a photocatalyst for the degradation of methylene blue in aqueous solution under visible irradiation. The photocatalytic degradation rate of methylene blue onto the synthesized ZnCo2O4 was higher than that of commercial ZnO and synthesized ZnO template.